Spatiotemporal variations of water conservation function based on EOF analysis at multi time scales under different ecosystems of Heihe River Basin. (1st January 2023) - Wu, Qiong; Song, Jinxi; Sun, Haotian; Huang, Peng; Jing, Kexing; Xu, Wenjin; Wang, Huiyuan; Liang, Dong
Abstract: Water conservation function is a critical terrestrial ecosystem service in providing water supply and achieving water security, which has raised concerns under the pressure of climate change. However, the knowledge of variance on multi-time scale, spatiotemporal dynamic, and ecosystem variance of water conservation is insufficient. In this paper, the annual, monthly, and daily scales of water conservation and the spatiotemporal pattern of monthly water conservation were estimated based on the SWAT model from 2010 to 2020 in the Heihe River Basin (HRB). Additionally, EOF (Empirical orthogonal function) analysis was conducted to decompose the time series of water conservation function distribution into temporal coefficients and spatial patterns. The HRB was categorized into six representative ecosystems with three slope grades to illustrate the variance of water conservation function. The annual water conservation depth (WC) slightly decreased (−10.36 mm/10a) from 2010 to 2020, the monthly WC was dominated by the effects of seasonal variation, and the daily WC was highly nonlinear. The high variability and importance region is mainly located in the upstream and the central area of midstream, which deserves more attention for ecological management and priority protection. Moreover, the forest ecosystem is of the highest resilience and great ecological significance, which increased risk of reduced water conservation under the lack of precipitation. Even in a forest-dominated basin, water conservation can be impacted by other ecosystems with the strong influence of human activities. Our results provide scientific evidence for the improvement of water conservation capacity and making the adapted land use policy in Yellow River basins. Highlights: Variances of water conservation in multi-time scales were analyzed. The dominant spatiotemporal patterns of water conservation were identified. Add variability with importance to delineate water conservation protection areas. Forest ecosystems could increase the risk of reduced water conservation in dry.